Improving Communication in Adolescent Cancer Care: A Multiperspective Study. Issue 8 (15th April 2016) - Essig, Stefan; Steiner, Claudia; Kuehni, Claudia E.; Weber, Heidemarie; Kiss, Alexander
Abstract : Background: Professionals treating adolescents with cancer must communicate well with them and their parents. Evidence suggests that the communication needs of this population are rarely met. Skills training can improve professional communication, but has been criticized for not being based on the experience of the participants in the clinical encounter. We took a multiperspective approach, drawing on perspectives of former adolescents with cancer, patients' parents, physicians, and nurses with the aim to provide suggestions for improvement in communication in adolescent cancer care. Methods: Adolescent cancer survivors (n = 16), parents (n = 8), pediatric oncologists (n = 12), and pediatric oncology nurses (n = 18) participated in 11 focus groups. They discussed their experiences communicating with each other. Transcripts were analyzed by thematic analysis. Results: We identified themes within the following sections: (1) The framework in which professionals communicate with adolescents with cancer (regression in a time of detachment, adolescents' perception and knowledge of illness, cognitive versus legal maturity, "lost in transition" between pediatric and adult oncology); (2) communication difficulties between professionals and patients and parents (professionals and patients/parents identified the other party as the source of difficulties), and (3) effective professional communication (there was some overlap on how doctors and nurses should communicate, along with substantially different expectations for the two professions). Conclusions: The framework within which professionals communicate, the different perspectives on the factors that make communication difficult, and the different expectations regarding good communication by doctors and nurses should be considered when communication skills training courses are developed for professionals who work in adolescent oncology.